Health Education About Anaemia in the RESSPRO Program (Healthy and Productive School Youth) at Himah Cipta Karsa Vocational School Garut - Iwan Shalahuddin; Indra Maulana; Theresia Eriyani; Sandra Pebrianti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Anaemia is a condition where the number of red blood cells or haemoglobin (Hb) is less than the normal value. The cause of anaemia is inadequate intake of nutrients. It can be caused by several factors: the wrong diet that interfere with iron absorption, lack of knowledge, unsupportive attitudes, maternal education, and the socioeconomic level of the family. In addition, adolescent girls often suffer anaemia because they are in a growing period that needs higher nutrients. Furthermore, they also experience menstruation every month and lack iron intake in the food consumed every day. Education aims to provide and improve students' understanding of preventing anaemia and identify the importance of early detection to avoid anaemia. The method used in this study was the lecture method, question and answer, discussion, and demonstration. The health education activities participants were 182 students. The counselling participants were enthusiastic and happy when presenting the material in progress. Conducive counselling activities because participants pay close attention to the material presented. It is evidenced by the number of participants interested in answering questions during the question-and-answer session. Participants participated in the counselling happily because the counselling was carried out with a pleasant face-to-face method. Conducive counselling activities because participants pay close attention to the material presented.